Optimization of supplier selection by using zero-one goal programming / Nur Ain Syuhada Azmali, Nor Atikah Anatasya Alias and Fatin Ainaa Azni Marzuki - Azmali, Nur Ain Syuhada; Alias, Nor Atikah Anatasya; Marzuki, Fatin Ainaa Azni (2018)
Supplier selection process is an important issue in business as well as supply chain system as most of the companies work with several suppliers in running the business. Nowadays, the suppliers need to compete with each other to gain trust from the company. However, the company also needs to choose the right supplier based on their qualitative and quantitative aspects. The task of choosing the right supplier is a tedious decision making process as it involves multiple objectives to be achieved. In this study, Zero-One Goal Programming (ZOGP) method was used to choose the best supplier for Az-Zain Mart which is situated in Shah Alam. ZOGP method was an approach to assist decision makers to solve multiple objective problems regarding this optimization problem of supplier selection. This study had helped Az-Zain Mart, Shah Alam in choosing the best supplier out of four suppliers, which were Nur Izam, R Razy Enterprise, Flytechnobiz or Ikhwan Food Industries in supplying fish ball by using ZOGP model. Then the model was tested using LINGO software by considering multiple constraints such as demand, purchasing cost, maximum supply delay time, transportation cost, defect ratio, delivery time and percentages of discount of the product. In the light of this result, the model was verified by using TOPSIS method where the best supplier for the company is R Razy Enterprise which achieved the objectives that had been set by the company. Thus, this showed that ZOGP was a useful tool that can be used to solve supplier selection problem as well as other multi-objectives problem.